Live Digital, Remember Digital: State of the Art and Research Challenges (2014)
The so called trend “live digital, remember digital” is acquiring higher relevance within the international research community, due to its several appealing challenges in a multitude of different fields within the Information and Communication Technologies. Today, many people live daily connected to the Internet through their mobile phones, laptops, tablets, etc. and the need to audit or log every single digital interaction emerges in many environments. By seamlessly recording those digital interactions and storing them in a privacy-preserving fashion, a number of benefits are brought to end users, like the provision of user-tailored services, amongst many others. In this paper we will particularly focus on the study of the security and privacy challenges within this field, as well as on the analysis of the currently existing solutions addressing these issues and we will propose an architecture for the so called live digital systems.